Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.iecr.6b00323
|View full text |Cite
|
Sign up to set email alerts
|

Design of Micro- and Milli-Channel Heat Exchanger Reactors for Homogeneous Exothermic Reactions in the Laminar Regime

Abstract: Considerable efforts have been made to study heat exchanger microreactors. However, the starting point in design for the selection of an adequate length scale that takes into account both the maximum temperature rise and pressure drop, important criteria for the holistic design of such equipment, is still missing. An attempt has been made in the present communication to provide such relationship over a wide range of operating variables. Fast and simple guidelines are discussed for beginning to design a heat ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The two flow arrangements modeled in this paper are also given in Figure 1. In such a heat exchange design, efficient heat exchange within the small-scale system is possible [47][48][49]. Recent studies have demonstrated that the management of energy in a small-scale confined space is one of the great challenges in design [50,51].…”
Section: Description Of the Reaction Systemmentioning
confidence: 99%
“…The two flow arrangements modeled in this paper are also given in Figure 1. In such a heat exchange design, efficient heat exchange within the small-scale system is possible [47][48][49]. Recent studies have demonstrated that the management of energy in a small-scale confined space is one of the great challenges in design [50,51].…”
Section: Description Of the Reaction Systemmentioning
confidence: 99%
“…The dimensions of these reactors often lie in the transition range between truly micrometer (up to 1 mm) and millimeter structured objects. [ 43 ] Tubular flow reactors in the micro‐ or millimeter scale made of polymers or steel are cost‐effective and can be easily modified to fit the process. They can be used to achieve longer residence times in space‐saving designs compared to macroscopic flow reactors.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic plate reformer needs careful design to avoid flow maldistribution, a typical pathology, for uniform reaction conditions in each channel and higher reforming efficiency in the reformer . Any flow maldistribution can lead to burning more methane in one or more channels, misalignment of reaction zones, hot spot formation, overheating, and significantly lower reformer performance. , A two-dimensional (2D) view of the velocity profile in the flow area of the CPR is shown in Figure a–c for an average channel inlet velocity at 1.4, 32.2, and 57.3 m/s, respectively. More data in terms of channel inlet velocity and velocity profiles are shown in Table S3 and Figure S1.…”
Section: Resultsmentioning
confidence: 99%